2013
DOI: 10.2196/med20.2720
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Social Media: Expectations of Users in a Developing Country

Abstract: BackgroundAffordability, acceptability, accommodation, availability, and accessibility are the five most important dimensions of access to health services. Seventy two percent of the Indian population lives in semi-urban and rural areas. The strong mismatched ratio of hospitals to patients, rising costs of health care, rapidly changing demographics, increasing population, and heightened demands in pricing for technological health care usage in emerging economies necessitate a unique health delivery solution mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Although our review identified 12 articles with a geographical focus in Asia, the evidence stemming from middle-income countries was scarce, and there were no studies from a low-income country. However, digital health initiatives are becoming more common in developing countries, often with a different, context-specific scope, such as ensuring access to health care using social media [ 102 ]. To ensure safe and effective use of solutions developed in HIC settings, there is a need for more research to corroborate the safety, effectiveness, and acceptability of these agents in LMICs too.…”
Section: Discussionmentioning
confidence: 99%
“…Although our review identified 12 articles with a geographical focus in Asia, the evidence stemming from middle-income countries was scarce, and there were no studies from a low-income country. However, digital health initiatives are becoming more common in developing countries, often with a different, context-specific scope, such as ensuring access to health care using social media [ 102 ]. To ensure safe and effective use of solutions developed in HIC settings, there is a need for more research to corroborate the safety, effectiveness, and acceptability of these agents in LMICs too.…”
Section: Discussionmentioning
confidence: 99%
“…focused on the expectations and assumptions of consumers of social media, four of which were published in 2016 and two in 2017. Four research articles targeted the general public [15,26,39,53] another study sampled a stakeholder group of healthcare professionals in Nigeria for their perceptions of the use of social media for healthcare delivery in their state [54]. Two other papers focused more specifically on consumers accessing information for specific health issues: palliative care [59], and an anti-tobacco campaign [34].…”
Section: Expectations and Assumptions Of Consumers Seven Articles (18%)mentioning
confidence: 99%
“…Although MXit use was low overall, study participants indicated willingness to interact with their peers on social media and suggested improvements for the MXit platform, using a more popular platform such as Facebook, and to include pertinent topic discussion for their specific population and context. 15 Horter et al 2014…”
Section: Appendix Amentioning
confidence: 99%
See 1 more Smart Citation
“…The increased popularity trend of the Internet usage, including social media as one of main communication means, repeatedly influences its employment and utilization for the sake of promoting pro-health behavior (Amrita, Biswas, 2013). Social media realize efficient and effective promotion, often based on information which is attractive to its receiver (Whittemore, Jeon, Grey, 2013).…”
Section: Introductionmentioning
confidence: 99%